Analysis of Problems Faced by Career Women and the Role of Counselors in Overcoming Them: Literature Review - Mawarda Zaimi; Lisa Putriani; Afdhal Afdhal; Nurfarhanah Nurfarhanah (Universitas PGRI SUMATERA BARAT, 2024)
The existence of career women in today's society is commonplace in line with developments in the era that have accustomed women to playing dual roles such as working outside the home and taking care of the household. This condition makes career women have greater responsibilities in their lives. With large responsibilities, many career women experience difficulties in dealing with various work and household problems, which can cause various psychological problems such as stress, depression and excessive anxiety. For this reason, the existence of a career counselor is needed to assist in the process of alleviating the problems of career women. This research aims to analyze the problems faced by career women and look at the role of counselors in overcoming them. This analysis uses a literature review approach. The results obtained from this review are that the problems of career women arise because of the many roles and functions of women in their lives, including as a wife, as a housewife, as successor of offspring, as a household manager and as a citizen. The problem of gender differences is a barrier for career women to develop their potential. Apart from being a worker, a career woman cannot be separated from her inherent identity as a wife, mother to her children and role model for those around her. In this case, counselors can design guidance and counseling services to help deal with problems faced by career women, counseling services regarding gender equality and multicultural counseling can be alternatives in providing assistance to career women with their problems.